1964
DOI: 10.1126/science.144.3624.1334
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Ash from Mount Mazama (Crater Lake) and from Glacier Peak

Abstract: New petrographic and chemical data indicate that the great Mount Mazama eruption at Crater Lake, Oregon, about 6600 years ago was the source of most ash which has been called "Glacier Peak" and of some ash called "Galata." Glacier Peak volcano in Washington was itself the source of an older ash deposit, perhaps very late glacial or early postglacial in age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 3 publications
3
61
0
Order By: Relevance
“…Its age, thickness, and grain size are all consistent with what woctld be expected in this region for the Mazama ash, which covers much of the Pacific Northwest (Powers and Wilcox, 1964), and Wilcox (oral commun., 1962) has confirmed that it is petrographically similar to the Mazama ash. Thus, layer 0 is regarded to be a part of the Mazama tephra blanket that is near the western limit of distribution now recognized for that tephra ( fig.…”
Section: Source and Agesupporting
confidence: 53%
“…Its age, thickness, and grain size are all consistent with what woctld be expected in this region for the Mazama ash, which covers much of the Pacific Northwest (Powers and Wilcox, 1964), and Wilcox (oral commun., 1962) has confirmed that it is petrographically similar to the Mazama ash. Thus, layer 0 is regarded to be a part of the Mazama tephra blanket that is near the western limit of distribution now recognized for that tephra ( fig.…”
Section: Source and Agesupporting
confidence: 53%
“…No particular problems are encountered for correlation between sites where tephra that represent the eruption of large volumes of material over wide areas are deposited. Powers & Wilcox (1964) cite an example of distinction between two tephra in the western United States by direct comparison of the major element analyses of rhyolitic glass. Borchardt & Harward (1971) suggested that such correlation is less likely to be successful in distinguishing between glasses from upper soil horizons where they have been more exposed to weathering and contamination.…”
Section: Single Component (Multiparticle) Methodsmentioning
confidence: 99%
“…), which occurred about6,600 years ago (Powers andWilcox, 1964, p. 1334;Wilcox, 1965, p. 810). Our sample is from the eastern of the two Mazama-ash localities in Nevada shown on the maps in the two reports (Powers and Wilcox, 1964, fig. 2; Wilcox, 1965, fig.…”
Section: Alluvium and Colluviummentioning
confidence: 99%